Character development based on hidden curriculum at the disaster-prone school - Zalik Nuryana; Suyadi Suyadi (Intelektual Pustaka Media Utama, 2019)
The character education development through hidden curriculum at disaster-prone schools possesses its own uniqueness with challenging complexity level. Amazing character education values should clash with appalling natural phenomenon. The objective of this research is to describe the character development through hidden curriculum in the volcanology disaster-prone area of Merapi mountain. This research was conducted on July-December 2017. Qualitative approach is utilized in this research. The data collection technique is performed using participants’ observation, in-depth interview, and documentation. The data analysis technique is performed descriptively, interpretatively and comparatively. The result of research indicates that (1) Muhammadyah Pakem Elementary School implements hidden curriculum related to character development, (2) The Hidden Curriculum is designed to develop character and instill disaster element because it is located in disaster-prone area, (3) the implementation of hidden curriculum concerning the disaster elements at school is able to provide knowledge and skill in early age related to disaster management to reduce the numbers of victims when the disaster occurs.